The Methodology of Ijtihād Tat̟bi̟qi̟ KH. Sahal Mahfudh - Taufiqur Rohman (Santri: Journal of Pesantren and Fiqh Sosial, 2021)
This article aims to examine the methodology of Ijtihād tat̟bīqī KH. Sahal Mahfudh in contextualizing and actualizing classical fiqh texts. The method used is qualitative with the theoretical approach of ijtihād tat̟bîqî by Abû Ishâq Ibrâhîm al-Syâtibi and the theory of Social Construction of Peter L. Berger and Thomas Luckmann with the basis of the Sociology of Knowledge analysis. The results of this study indicate that there are three methodologies of Ijtihād tat̟bīqī KH. Sahal Mahfudh: first, historical approach. Second, the cultural approach (culture), Third, the sociological approach. The contribution of this research is to actualize and contextualize classical fiqh texts while maintaining their relevant authenticity and then synergizing them with more positive modern scientific disciplines so that they exist and survive in the present and as the future development of Indonesian and world fiqh.